ANALISIS HUKUM PADA PUTUSAN HAKIM TERHADAP HAK HADHANAH KEPADA BAPAK BAGI ANAK BELUM MUMAYIZ (Analisis Putusan Pengadilan Agama Kabupaten Malang Perkara Nomor 2671/Pdt.G/2021/PA.Kab.Mlg) - Mauliddan Mauliddan; Syamsu Madyan; Moh. Muslim (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
Marriage has a purpose, including to produce offspring, every child born must have a biological mother and father that causes its existence. The presence of children in a marriage is a right that every couple dreams of, for them it is an extraordinary gift from God, he must be guarded and cared for as well as possible. However, sometimes marriages do not always go as expected, so that various problems arise, including divorce which causes a fuss over child custody. This is usually a difficult problem because the two divorced parents can fight each other for custody of the child to whom the child is given depending on the consideration of the panel of judges. Researchers formulate problems aboutthe ijtihad methodist of the paneI judes in decidng thee casee the child's hadhanah rights to the fatherandthe basis of legal considerations used by the panel of juddges indeciding tthe cased.This study aims to describe thethe ijtihad method of the panel of judges in deciding the case of the child's hadhanah rights to the father, andthe bassis in Iegal consideration useful bye the panel of jadges on decilding on cased. The research uses a case study approach. Researchers used data collection techniques, namely byhow to copy the decision and then analyzed by the author, interviews and literature review.